Tonsillar tuberculosis, with primary pulmonary focus: A Case Report - Lugo Machado, Juan Antonio (2015)
Tuberculosis is an infectious disease that affects various organs and tissues, with greater tropism for lung disease, gastrointestinal and central nervous system tissue and even bone. However isolated cases of affection to other structures have been reported, just like this patient who came with symptoms in the tonsils and subsequently, lung involvement became apparent. Theton sillar infection in this case was considered a secondary tuberculosis with primary focus in the lungs.